(untitled) (Información, cultura y sociedad, 2008)
This work shows a brief report about the academic activities that were carried out at the International Congress «Texts, authors and libraries», in Córdoba city on 24-26 September, 2008, on the occasion of the 190 years of the opening of the Biblioteca Mayor of Universidad Nacional de Córdoba.